Pemenuhan Hak Politik Penyandang Disabilitas Melalui Perekaman e-KTP dalam Pengelolaan Daftar Pemilih Pemilu - Luh Eka Sudiarini; Komang Febrinayanti Dantes; Ni Ketut Sari Adnyani; I Nyoman Budiada (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the fulfillment of the political rights of people with disabilities through the issuance of electronic identity cards (e-KTP) in the management of the voter registry. Political rights are part of human rights, and their fulfillment must be guaranteed without discrimination, including for people with disabilities. The issuance of e-KTPs is a key requirement in civil registration that influences the determination of the permanent voter list, thereby playing a strategic role in ensuring citizens’ political participation. This study employs a normative legal method using both a statutory and a conceptual approach. Research data were obtained through a literature review of laws and regulations, scholarly literature, and documents related to population administration and the conduct of elections. The results show that e-KTP registration plays a crucial role in guaranteeing the political rights of people with disabilities, as it serves as the basis for compiling the voter list. Therefore, inclusive, accessible, and nondiscriminatory population administration services are necessary to ensure democratic and fair elections that provide equal opportunities for all citizens.